Bimolecular reactions of S2+ with Ar, H2 and N2: reactivity and dynamics. Issue 14 (24th March 2022) - Armenta Butt, Sam; Price, Stephen D.
Abstract : The bimolecular reactivity and reaction dynamics following collisions of S 2+ with Ar, H2 and N2 are investigated. The reactivity is dominated by electron transfer reactions, but the formation of SN + is also detected following S 2+ collisions with N2 . Abstract : The reactivity, energetics and dynamics of bimolecular reactions between S 2+ and three neutral species (Ar, H2 and N2 ) have been studied using a position-sensitive coincidence methodology at centre-of-mass collision energies below 6 eV. This is the first study of bimolecular reactions involving S 2+, a species detected in planetary ionospheres, the interstellar medium, and in anthropogenic manufacturing processes. The reactant dication beam employed consists predominantly of S 2+ in the ground 3 P state, but some excited states are also present. Most of the observed reactions involve the ground state of S 2+, but the dissociative electron transfer reactions appear to exclusively involve excited states of this atomic dication. We observe exclusively single electron-transfer between S 2+ and Ar, a process which exhibits strong forward scatting typical of the Landau–Zener style dynamics observed for other dicationic electron transfer reactions. Following collisions between S 2+ + H2, non-dissociative and dissociative single electron-transfer reactions were detected. The dynamics here show evidence for the formation of a long-lived collision complex, [SH2 ] 2+, in the dissociative single electron-transfer channel. The formation of SH + was not observed. In contrast, the collisions of S 2+ + N2 result in the formation of SN + + N + in addition to the products of single electron-transfer reactions.